GENDER INEQUALITY: A SOCIAL EVIL - H. Tabassum; M. Ashfaq; R. Kousar; A. Saghir; R. Amjad (Journal of Animal and Plant Sciences, 2010)
The aim of the present study was to explore the status of women in the country and also to study the effect of discrimination against women. Women education is very important for the development of a nation. They have an active participation in every field especially in several income generating activities like agriculture, livestock, medicine, education and handicrafts making. They contribute greatly toward family and country’s economy. They need proper training and brought up for the well being of coming generations. The present study was conducted in rural areas of district Faisalabad. Two hundred respondents were selected by multi-stage sampling technique. The data were collected through pre-tested and validated interview schedules and were analyzed using Statistical Package for Social Sciences (SPSS) to draw conclusions and to suggest measures for improvement. The results of present study showed that women education at rural areas is very meager and people dislike the modernization and liberty. But new generation think that education play significant role in human development.
Keywords: Gender; inequality; multistage sampling technique; liberty; social evil